Validation of the Hungarian version of the General Oral Health Assessment Index (GOHAI) in clinical and general populations - Judit Oszlánszky; Károly Mensch; Péter Hermann; Zsombor Zrubka (BMC, 2024)
Abstract Background COSMIN (Consensus-based Standards for the selection of health Measurement INstruments) provides a framework for selecting and validating patient-reported outcome measurements (PROMs). This study aims to validate the Hungarian version of the GOHAI and, for the first time, to assess its Standard Error of Measurement (SEM), Smallest Detectable Change (SDC), and Measurement Invariance (MI) across general and clinical populations as well as different age groups, following COSMIN guidelines. Materials and methods The translation was performed using a forward-backward process. A mixed sample (n = 306) was recruited in Budapest from May 2023 to February 2024, consisting of the general population (45.1%), recruited from health kiosks and a nursing home, and the clinical population (54.9%), sourced from Semmelweis University's care units. The sample was further divided into two age groups: 18-64 years old (54.9%) and 65 + years old (45.1%). GOHAI was administered twice to 108 stable participants. For both the additive score (ADD-GOHAI) and simple count (SC-GOHAI), structural validity and measurement invariance by subgroups were assessed via Confirmatory Factor Analysis (CFA). Internal consistency was evaluated using Cronbach's alpha, and test-retest reliability was measured using the intraclass correlation coefficient (ICC). SEM was calculated using the SEM agreement formula, and SDC using: $$\:SDC=1.96*\sqrt{2}*SEM$$ . Convergent and known-group validity were tested against predefined hypotheses for structural validity. Results Contrary to a three factor model, a single-factor model showed good fit in all subgroups for both scoring methods, with adequate internal consistency (Cronbach 𝛼: 0.76-0.85). Four of the six hypotheses for convergent validity and all ten hypotheses for known-groups validity supported the predefined criteria. Measurement invariance between clinical and general populations, or by age, was not demonstrated, so GOHAI's different measurement properties should be considered when comparing subpopulations. Test-retest reliability was adequate (ICC: 0.87-0.96). SDC was ≈5 points using ADD-GOHAI and 2-3 points using SC-GOHAI. Conclusion The Hungarian version of GOHAI demonstrates satisfactory psychometric properties across both general and clinical populations, as well as among both younger and older age groups. While the measurement properties of SC-GOHAI may be more stable between populations, ADD-GOHAI seems more suitable for individual follow-up. However, observed changes must be considered in relation to the measurement error associated with GOHAI.